2014
DOI: 10.1111/tri.12397
|View full text |Cite
|
Sign up to set email alerts
|

Gender has no influence on VUR rates after renal transplantation

Abstract: SummaryThe influence of recipient gender on urological complications including vesicoureteral reflux (VUR) after renal transplantation has not yet been established. In this study, post-transplantation voiding cystourethrography and ultrasonography were used to evaluate the upper and lower urinary tract in 598 consecutive renal transplant recipients. Our cohort included 209 females and 389 males, respectively. Gender-specific urological complications and potential confounders were analyzed in relation to long-t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 33 publications
0
4
0
1
Order By: Relevance
“…The highest incidence has been reported within 6 months following KT, likely related to surgical manipulation and concurrent use of immunosuppressive treatment 12 . Some patients experience recurrent UTIs during this period with a prevalence between 4% and 72% 13,14 . In addition to immunosuppression, KT patients have mechanical risk factors for UTIs.…”
Section: Introductionmentioning
confidence: 99%
“…The highest incidence has been reported within 6 months following KT, likely related to surgical manipulation and concurrent use of immunosuppressive treatment 12 . Some patients experience recurrent UTIs during this period with a prevalence between 4% and 72% 13,14 . In addition to immunosuppression, KT patients have mechanical risk factors for UTIs.…”
Section: Introductionmentioning
confidence: 99%
“…In their study, no differences were observed between experienced and inexperienced surgeons [28]. On the contrary, a multivariate analysis by Farr et al has shown that surgical experience is the most significant predictor of post-transplant VUR, even after multiple adjustments for potential confounders and sex-specific urological complications [15].…”
Section: Surgical Technique For Ureteral Implantation Surgical Expertisementioning
confidence: 76%
“…Most literature suggests that females may be more prone to allograft VUR and UTIs [11][12][13][14]. However, in a study specifically designed to assess the effect of sex on VUR, Farr et al observed that, on multivariate analysis, no sex-specific differences could be detected [15].…”
Section: Epidemiology Etiology and Risk Factors For Post-transplant Vurmentioning
confidence: 99%
“…5,[10][11][12] Entre los factores de riesgo para reflujo vesicoureteral se encuentran: capacidad vesical disminuida previa al trasplante y falta de experiencia del cirujano. 1,13 Los pacientes con infección de vías urinarias después del trasplante renal tienen mayor riesgo de pérdida del injerto y mortalidad. 14 Dupont y su grupo encontraron que los pacientes con infección de vías urinarias y reflujo vesicoureteral posterior a trasplante renal tuvieron mayor incidencia cicatrices renales que quienes no tuvieron reflujo.…”
Section: Antecedentesunclassified